Integration of Chemical and Manual Weed Management on Weed Density, Yield and Production Economics of Lentil (Lens culinaris Medikus) - Lhungdim, J.; Singh, Y.; Singh, R. Pd. (International Journal of Bio-resource and Stress Management, 2023)
A field study was conducted during rabi, 2010-11 and 2011-12 at Agricultural Research farm, BHU, Varanasi (U.P.) where five herbicides either as sole, integrated with mechanical weeding (MW) or sequentially applied were evaluated for efficacies of the herbicides on controlling weeds, their influences on yield and production economics on lentil (Lens culinaris Medikus) variety HUL 57. Results revealed that, two hand weeding (HW) was the most effective method for weed control next to weed free. At 60 DAS however, lowest density and dry matter accumulation of all weed species were recorded with two hand weeding at 30 and 45 DAS followed by sequential/continuous application of Pendimethalin (PE) and Imazethapyr (post-emergence/POE) that remained statistically at par with Pendimethalin+MW in the case of BLWs and grasses and Chlorimuron ethyl+MW in respect of sedges. Maximum weed control efficiency (WCE) was achieved under two HW (83%) followed by Pendimethalin+MW at 45 DAS and continuous application of Pendimethalin+Imazethapyr (76% each). However, significantly highest yield (1365 kg ha-1), highest pods plant-1 (66.07), seeds pod-1 (1.94) and nodules plant-1 (8.20) were recorded under Pendimethalin+MW which was comparable and significantly not different from Pendimethalin+Imazethapyr @ 37.5 g a.i. ha-1. Among sole applications, Pendimethalin and Pendimethalin+Imazethapyr (pre-mixed) significantly suppressed broadleaved weeds but poorly controlled the sedges and grasses though it was better than control. In the economic factor, Pendimethalin+MW with highest net return and benefit:cost ratio (` 47521 ha-1 and 3.15) and lowest weed index (4.51) was comparatively better than all the treatments including control. This integrated treatment was found as the most profit-oriented and sustainable weed management system in lentil.